2023
DOI: 10.3390/ijms24021371
|View full text |Cite
|
Sign up to set email alerts
|

The Synergic Effect of AT(N) Profiles and Depression on the Risk of Conversion to Dementia in Patients with Mild Cognitive Impairment

Abstract: Few studies have addressed the impact of the association between Alzheimer´s disease (AD) biomarkers and NPSs in the conversion to dementia in patients with mild cognitive impairment (MCI), and no studies have been conducted on the interaction effect of these two risk factors. AT(N) profiles were created using AD-core biomarkers quantified in cerebrospinal fluid (CSF) (normal, brain amyloidosis, suspected non-Alzheimer pathology (SNAP) and prodromal AD). NPSs were assessed using the Neuropsychiatric Inventory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This study has been conducted within the ACE cohort, which consists of MCI men and women aged > 48 years recruited and assessed between 2006 to 2022 at the Memory Disorders Unit (ACE Alzheimer Center, Spain). Patients were diagnosed with MCI at a case conference attended by neurologists, neuropsychologists, and social workers, and using the Spanish version of the Mini-Mental State Examination (MMSE), the memory part of the Spanish version of the 7 Minute test, the Spanish version of the Neuropsychiatric Inventory Questionnaire (NPI-Q), the Hachinski Ischemia Scale, the Blessed Dementia Scale and the Clinical Dementia Rating (CDR) scale, as well as a comprehensive neuropsychological battery of ACE (N-BACE) [ 25 ] Detailed characteristics of the study population can be found elsewhere [ 26 ]. From a total of 361 participants with MCI, free of type 2 diabetes, who had ATN classification, available plasma samples and follow-up data, 211 individuals were classified as A+(T|N)+ .…”
Section: Methodsmentioning
confidence: 99%
“…This study has been conducted within the ACE cohort, which consists of MCI men and women aged > 48 years recruited and assessed between 2006 to 2022 at the Memory Disorders Unit (ACE Alzheimer Center, Spain). Patients were diagnosed with MCI at a case conference attended by neurologists, neuropsychologists, and social workers, and using the Spanish version of the Mini-Mental State Examination (MMSE), the memory part of the Spanish version of the 7 Minute test, the Spanish version of the Neuropsychiatric Inventory Questionnaire (NPI-Q), the Hachinski Ischemia Scale, the Blessed Dementia Scale and the Clinical Dementia Rating (CDR) scale, as well as a comprehensive neuropsychological battery of ACE (N-BACE) [ 25 ] Detailed characteristics of the study population can be found elsewhere [ 26 ]. From a total of 361 participants with MCI, free of type 2 diabetes, who had ATN classification, available plasma samples and follow-up data, 211 individuals were classified as A+(T|N)+ .…”
Section: Methodsmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive cognitive decline and memory impairment [1,2]. Mild cognitive impairment (MCI) represents a transitional stage between normal aging and dementia due to AD (AD dementia), and a substantial proportion of individuals with MCI eventually progress to develop AD dementia [3,4].…”
Section: Introductionmentioning
confidence: 99%